Impact of hypothermia on the biomechanical effect of epithelium-off corneal cross-linking - Abdshahzadeh, Hormoz (Eye Vis (Lond), 2021)
BACKGROUND: The corneal cross-linking (CXL) photochemical reaction is essentially dependent on oxygen and hypothermia, which usually leads to higher dissolved oxygen levels in tissues, with potentially greater oxygen availability for treatment. Here, we evaluate whether a reduction of corneal temperature during CXL may increase oxygen availability and therefore enhance the CXL biomechanical stiffening effect in ex vivo porcine corneas. METHODS: One hundred and twelve porcine corneas had their epithelium manually debrided before being soaked with 0.1% hypo-osmolaric riboflavin. These corneas were equally assigned to one of four groups. Groups 2 and 4 underwent accelerated epithelium-off CXL using 9 mW/cm(2) irradiance for 10 min, performed either in a cold room temperature (group 2, 4 °C) or at standard room temperature (group 4, 24 °C). Groups 1 and 3 served as non-cross-linked, temperature-matched controls. Using a stress-strain extensometer, the elastic moduli of 5-mm wide corneal strips were analyzed as an indicator of corneal stiffness. RESULTS: Accelerated epithelium-off CXL led to significant increases in the elastic modulus between 1 and 5% of strain when compared to non-cross-linked controls (P < 0.05), both at 4 °C (1.40 ± 0.22 vs 1.23 ± 0.18 N/mm) and 24 °C (1.42 ± 0.15 vs 1.19 ± 0.11 N/mm). However, no significant difference was found between control groups (P = 0.846) or between groups in which CXL was performed at low or standard room temperature (P = 0.969). CONCLUSIONS: Although initial oxygen availability should be increased under hypothermic conditions, it does not appear to play a significant role in the biomechanical strengthening effect of epithelium-off CXL accelerated protocols in ex vivo porcine corneas.